Results of Comparison of Two Types of Olfactory Recognition Tests Performed on 112 Peoples. - 34 High School Students, 55 University Students, and 23 Middle-Aged (Global Journal of Medical Research, 2020)
The olfactory cognitive test is not commonly used. Still, it required in the future because it reported that and olfactory disorder appears as an initial symptom of Alzheimer's dementia or COVID-19 infection. There are several types of odor inspection kits used for testing, but in Japan, there are odor sticks, open essences, T&T olfactometry, etc. This time, we report that we conducted an olfactory cognitive test using Odor Sticks and Open Essence on healthy 112 peoples (34 high school students, 55 university students, and 23 middle-aged). The Open Essence (made by FUJIFILM) has the smell as same as the Odor Stick Identification Test (OSIT-J). The odor Stick (made by Daiichi Pharmaceutical industry Co., Ltd.) and the open essence include the aromas as curry, perfume, Japanese cypress, India ink, menthol, rose, wood, stynkysocks/sweat, roasted garlic, condensed milk, gas for cooking, and Japanese mandarin aromas. This 12 different odorants perception is not necessarily culture-free; the Japanese version employed.
Keywords: olfaction test; odor stick; open essence; cognition; age